1971
DOI: 10.2307/2060620
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of the effects of socioeconomic development on fertility rates

Abstract: Recent studies by Adelman and by Friedlander and Silver, which have investigated whether regression equations derived from cross-section data can be used to predict the impact of socioeconomic development on changing levels of fertility, are reviewed critically. Regression analyses based on data for 57 countries c. 1960 show that fertility (gross reproduction rate) varies cross-sectionally with region as well as with level of development (as measured by per capita income, percent labor force in primary sector,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…Using the theory of demographic transition as a basic theoretical framework, numerous studies [Adelman, 1963;Ekanem, 1972;Friedland and Silver, 1967;Gregory et al, 1973;Heer, 1966;Janowitz, 1971;Janowitz, 1973;Kamerschen, 1971;Oechsli and Kirk, 1975;Russett, 1964;Weintraub, 1962] have investigated the relationships between fertility changes and demographic, economic, and social development. However, the findings of previous studies are not conclusive as to how demographic, economic, and social changes affect fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Using the theory of demographic transition as a basic theoretical framework, numerous studies [Adelman, 1963;Ekanem, 1972;Friedland and Silver, 1967;Gregory et al, 1973;Heer, 1966;Janowitz, 1971;Janowitz, 1973;Kamerschen, 1971;Oechsli and Kirk, 1975;Russett, 1964;Weintraub, 1962] have investigated the relationships between fertility changes and demographic, economic, and social development. However, the findings of previous studies are not conclusive as to how demographic, economic, and social changes affect fertility.…”
Section: Introductionmentioning
confidence: 99%
“…group. Such a problem has been frequently reported in demographic research (e.g., Friedlander and Silver, 1967;Janowitz, 1971;Ekanem, 1972;Beaver, 1975;Chang and Pendleton, 1978). In this study, homogeneous cultural groups of developing countries have been analyzed to avoid this statistical problem.…”
Section: Path Analysismentioning
confidence: 87%
“…A number of studies have found a statistically strong positive causal link between infant mortality and different measures of fertility (Weintraub, 1962:816, Bhattacharyya, 1975Massey and Tedrow, 1976:435;Som, 1978:16;Glassman and Ross, 1978:197). Other studies did not find consistent patterns of causation between infant mortality and fertility measures (Friedlander and Silver, 1967:53;Anker, 1978:68;Janowitz, 1971Janowitz, , 1973bGregory et al, 1973:236-240). Moreover, some studies did not find any significant support for the relationship (Ekanem, 1972;Janowitz, 1973a;Beaver, 1975;Hohm, 1975;Chang et al, 1979;Chang and Pendleton, 1978).…”
Section: Infant Mortalitymentioning
confidence: 90%
See 2 more Smart Citations